Modeling, design and thermal performance of a BIPV/T system thermally coupled with a ventilated concrete slab in a low energy solar house: Part 2, ventilated concrete slab - Chen, Yuxiang (2010)
This paper is the second of two papers that describe the modeling and design of a building-integrated photovoltaic–thermal (BIPV/T) system thermally coupled with a ventilated concrete slab (VCS) adopted in a prefabricated, two-storey detached, low energy solar house and their performance assessment based on monitored data. The VCS concept is based on an integrated thermal–structural design with active storage of solar thermal energy while serving as a structural component – the basement floor slab (∼33 m2). This paper describes the numerical modeling, design, and thermal performance assessment of the VCS. The thermal performance of the VCS during the commissioning of the unoccupied house is presented. Analysis of the monitored data shows that the VCS can store 9–12 kWh of heat from the total thermal energy collected by the BIPV/T system, on a typical clear sunny day with an outdoor temperature of about 0 °C. It can also accumulate thermal energy during a series of clear sunny days without overheating the slab surface or the living space. This research shows that coupling the VCS with the BIPV/T system is a viable method to enhance the utilization of collected solar thermal energy. A method is presented for creating a simplified three-dimensional, control volume finite difference, explicit thermal model of the VCS. The model is created and validated using monitored data. The modeling method is suitable for detailed parametric study of the thermal behavior of the VCS without excessive computational effort.